Analisis Minat Belajar Siswa pada Pembelajaran Daring Siswa Kelas IVA SD Negeri 1 Tertek Tulungagung - Puspitasari, Anggraini Dyah; Ana, Ria Fajrin Rizqy (Jurnal Simki Pedagogia, 2023)
Learning in the network (online) is a learning process that is carried out without meeting face to face and all forms of material are carried out online which makes student learning interest decrease. The type of research used in this study is qualitative research, while the approach in this study uses a descriptive approach. The purpose of this study was to describe students' interest in online learning experienced by class IVA students at SDN 1 Tertek Tulungagung. The subjects in this study were students of class IVA. Data collection techniques used in this study were questionnaires, interviews, and documentation. The first indicator is feeling happy to get a total score of 303 with a percentage of 56% included in the medium category. The second indicator of involvement gets a total score of 292 with a percentage of 54% included in the medium category. The third indicator of interest gets a total score of 245 with a percentage of 55% included in the medium category. The fourth indicator is attention which gets a total score of 232 with a percentage of 65% included in the high category. The conclusion of this study is that the final score results from the percentage per indicator of student interest in learning obtain a total score of 230 with a percentage of 57% included in the medium category.